INTEGRASI MAQASHID AL-SYARIAH DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM UNTUK MENJAWAB DILEMA ETIKA TEKNOLOGI DIGITAL - Rodian; Miftahul Jennah; Misnatun Hasanah; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
The development of the digital era has created new challenges for Islamic education, particularly in developing a curriculum that integrates technological advancement with Islamic values. This article aims to analyze the implementation of Al-Maqāṣid Al-Sharī‘ah principles in Islamic education curriculum as an effort to respond to changes and educational needs in the digital era. This study employs a library research method by examining relevant literature, academic journals, and educational documents. The findings indicate that Al-Maqāṣid Al-Sharī‘ah can serve as a foundation for curriculum development by strengthening religious values, improving intellectual development, building students’ character, and encouraging responsible use of technology. The implementation of principles such as ḥifẓ al-dīn (preservation of religion) and ḥifẓ al-‘aql (preservation of intellect) plays an important role in developing students who are not only digitally competent but also possess Islamic ethics and moral values. However, its implementation still faces challenges, including negative impacts of technology and changes in students’ behavior. Therefore, an adaptive curriculum development strategy is needed to ensure that Islamic education remains relevant in facing the demands of the digital era.